Visualization experiment and flow homogenization optimization of the multi-path plenum chamber system using a perforated plate. (1st April 2023) - Zhang, Wanqing; Li, Angui; Gao, Ran; Gao, Xin; Yang, Changqing
Abstract: Plenum chambers are commonly used to provide flow homogenization in ventilation and air conditioning systems. To reduce energy consumption and improve ventilation performance, the interior flow characteristics of a multi-path plenum chamber system were investigated through visualization experiments of flow field. As the flow distribution remained uneven after the primary structural parameters of the traditional chamber were optimized, a flow homogenization chamber was proposed by inserting a perforated plate to further improve flow uniformity. Taking the "one-inlet and two-outlet" chamber configuration as a case study, the proposed flow homogenization mechanism was analyzed in terms of flow control. The effects of the perforated plate geometry on flow uniformity and resistance performance were studied using two typical chambers with cross-sectional aspect ratio ( W/H ) of 1/1 and 5/1. The recommended dimensionless installation location of the perforated plate ( y/L ) in each chamber was determined to be 0.1 and 0.3 of the chamber length from the input, respectively, with an optimal aperture diameter ( d ) of 30 mm. In addition, the effectiveness of the flow homogenization chamber was verified using four commonly used air duct sizes, and different application scenarios were discussed for multi-path duct connections. The results show that the adjustment of perforated plate on flow field improved the flow distribution uniformity for chamber system with W/H  = 1/1 and 5/1 by up to 87.50% and 56.71%, respectively, compared with the standard 90° T-junction connection. Highlights: Airflow movement inside chamber is analyzed through visualization experiments. Inserting perforated plate can effectively improve the flow uniformity of chamber. Conversion between axial and radial flows is the most critical step for flow homogenization. The optimal installation location and aperture rate of perforated plate are obtained.